ผลของการสนับสนุนผู้ดูแลด้านข้อมูลและด้านอารมณ์ต่อการปฏิบัติกิจวัตรประจำวันและความผาสุกของผู้สูงอายุที่เป็นโรคหลอดเลือดสมองในระยะฟื้นฟูสภาพ - กุลธิดาพร กีฬาแปง (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Cerebrovascular disease, or stroke, is an acute neurological deficit. Survivors will have disabilities which place limitations on their activities of daily living (ADL) and impacts their well-being also. Caregivers have an important role in caring for their elderly stroke affected patients. The purpose of this experimental research was to evaluate the effects of information and emotional supports provided to caregivers relating to activities of daily living and well-being among the elderly with stroke and during rehabilitation phase. Subjects were caregivers and elderly with stroke who were admitted at medical and rehabilitation wards,MaharajNakorn Chiang Mai Hospital during May 2014 to July 2014. Fifty-one subjects were randomly assigned into control and experimental groups; 26 persons in the control group and 25 persons in the experimental group. The subjects in the experimental group received care according to information and emotional supports for caregivers, while those in the control group received routine support. Research instruments consisted of; 1) the information and emotional supports for caregivers plan, 2) the handbook for the caring of elderly stroke patients at home, and 3) vediotape of caring for paralysis patients due to stroke. The assessment tools consisted of Assessment Form of ADL Stroke Patients and Assessment Form of Well-being Ladder Scale. Data were analyzed by using descriptive statistics, independent t- test, and paired t - test. Research results revealed that: 1. The activities of daily living score of the experimental group was statistically significantly higher than that of the control group (p < .001); and 2. The well-being score of the experimental group was statistically significantly higher than that of the control group (p < .001) The results from this study indicated that information and emotional supports provided to caregivers could enhance activities of daily living and well-being among elderly with stroke. The researcher recommends that the information and emotional supports for caregivers should be used as a guideline in caring to help the elderly with stroke to enhance activities of daily living and their well-being effectively.